Empathy Modulates the Evaluation Processing of Altruistic Outcomes - Liu, Xin; Hu, Xinmu; Shi, Kan; Mai, Xiaoqin (Frontiers in Psychology, 2018)
Empathy plays a central role in social decisions involving psychological conflict, such as whether to help another person at the cost of one’s own interests. Using the event-related potential (ERP) technique, the current study explored the neural mechanisms underlying the empathic effect on the evaluation processing of outcomes in conflict-of-interest situations, in which the gain of others resulted in the performer’s loss. In the high-empathy condition, the beneficiaries were underprivileged students who were living in distress (stranger in need). In the low-empathy condition, the beneficiaries were general students without miserable information (stranger not in need). ERP results showed that the FRN was more negative-going for self no-gain than self gain, but showed reversed pattern for other’s outcome (i.e., more negative for gain than no gain) in the low-empathy condition, indicating that participants interpreted the gain of others as the loss of themselves. However, the reversed FRN pattern was not observed in the high-empathy condition, suggesting that the neural responses to one’s own loss are buffered by empathy. In addition, the P3 valence effect was observed only in the self condition, but not in the two stranger conditions, indicating that the P3 is more sensitive to self-relevant information. Moreover, the results of subjective rating showed that more empathic concern and altruistic motivation were elicited in the high-empathy condition than in the low-empathy condition, and these scores had negative linear correlations only with FRN, not P3. Taking this together, these suggest that when outcomes following altruistic decisions involve conflict of interest, the early stage of the processing of outcome evaluation could be modulated by the empathic level.